Thus says the Lord : essays on the Former and Latter Prophets in honor of Robert R. Wilson - Wilson, Robert R., 1942-; Ahn, John J.; Cook, Stephen L., 1962- (New York ; London : T & T Clark, 2009)
This work assembles contributions from North America''s leading Hebrew Bible/Old Testament scholars in honor of a highly respected biblical scholar, whose work on biblical prophets has been especially influential. Within the list are former teachers, current colleagues, and former students who are now colleagues in their own right, representing a wide range of denominational traditions represented-Roman Catholics, Lutheran, Episcopal, Presbyterian, etc. The book is divided into major two sections with a brief introduction by the editors, John Ahn and the Stephen Cook. Here, a brief biograph.
Introductory celebration of Robert R. Wilson / John Ahn and Stephen L. Cook -- Joshua son of Nun : presentation of a prophet / Stephen B. Chapman -- Religion in the heroic spirit : themes in the Book of Judges / Baruch A. Levine -- What is prologue is past : composing Israelite identity in Judges 5 / Mark S. Smith -- Judges, kingship, and political ethics : a challenge to the conventional wisdom / Susan Niditch -- Prophecy and theodicy / John Barton -- Authority to edify : verification of biblical truth in William Robertson Smith's Prophets of Israel / Warner M. Bailey -- The poetics of biblical prophecy : point of view and point of standing in the prophetic books / Harry P. Nasuti -- The poetry of creation / Robert B. Robinson -- "Daughter Zion" / F.W. Dobbs-Allsopp -- The beginning of the end of the world in the Hebrew Bible / John J. Collins -- Prophetic associations / Christopher R. Seitz -- (Re)inscribing power through Torah teaching : rhetorical pedagogy in the Servant Songs of Deutero-Isaiah / Carolyn J. Sharp -- Jeremiah and the Levitical priests of Anathoth / S. Dean McBride, Jr. -- Remembering the prophets / David L. Petersen -- Putting the mother back in the center : metaphor and multivalence in Ezekiel 19 / Corrine Carvalho -- The speechless suppression of grief in Ezekiel 24:15-27 : the death of Ezekiel's wife and the prophet's abnormal response / Stephen L. Cook -- Portraying prophetic experience and tradition in Ezekiel / D. Nathan Phinney -- "But if not--" what? : the speech of the youths in Daniel 3 and a (theo)logical problem / Roy L. Heller -- Myth and truth in socio-historical reconstruction of ancient societies : Hosea 4:11-14 as a test case / Christl M. Maier -- The social location(s) of Amos : Amos 1:3-2:16 / Gene M. Tucker -- Jonah and the uses of parody / William W. Hallo -- Zephaniah, a disciple of Isaiah? / John Ahn.
Includes bibliographical references and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible. -- Critique, interprétation, etc; Bible; Bible; Bibel; Wilson, Robert Rutherford; Geschichtsbücher -- (Altes Testament; Prophetische Bücher -- (Altes Testament; RELIGION -- Biblical Studies -- Old Testament; Aufsatzsammlung; Festschriften; Criticism, interpretation, etc; Festschriften